2020
DOI: 10.4314/sajas.v50i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient contents and in vitro digestibility of different parts of corn plant

Abstract: AbstractThe objective of this study was to assess the nutrient contents and in vitro true digestibility (IVTD) of parts of the corn plant. The corn used in the study was P2088, a variety that is grown widely in Turkey. It had matured and was harvested 140 days after planting. Four replicate plants were separated into nine parts, namely lower stalk, central stalk, upper stalk, corn ear stalk, corn ear shuck, kernels, corn cob, leaf, tassel, plus the entire plant. The samples were dried and ground for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
3
13
0
2
Order By: Relevance
“…According to Barrière et al (2005) findings, modern hybrids have an average 5.5% lower in vivo cell wall digestibility than older hybrids, despite a slight but considerable increase in the grain share in the overall maize plant. Ayaşan et al (2020), for instance, showed statistically significant differences in IVDMD between various portions of the maize plant, with the kernel having the highest IVDMD (79.06%) and the lower stalk having the lowest IVDMD (38.13%).…”
Section: Figure 2 Content Of the Lignocellulosic Fibers Of The Whole ...mentioning
confidence: 97%
See 1 more Smart Citation
“…According to Barrière et al (2005) findings, modern hybrids have an average 5.5% lower in vivo cell wall digestibility than older hybrids, despite a slight but considerable increase in the grain share in the overall maize plant. Ayaşan et al (2020), for instance, showed statistically significant differences in IVDMD between various portions of the maize plant, with the kernel having the highest IVDMD (79.06%) and the lower stalk having the lowest IVDMD (38.13%).…”
Section: Figure 2 Content Of the Lignocellulosic Fibers Of The Whole ...mentioning
confidence: 97%
“…It is simple to manufacture and preserve silage maize, and it can be consumed every day all year round (Barrière et al, 2018). Thanks to the growing progress of silage technology, whole maize plant is one of the most crucial feedstuffs for animals in the world today (Ayaşan et al, 2020). Developing hybrids with enhanced whole plant yield, nutritional value, and agronomic features that give superior ensiling quality has recently received a lot of attention in the breeding of silage maize (Terzić et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To determine in vitro dry matter digestibility (IVDMD), this experiment was carried out in accordance with Animal Ethics Committee of Research CIRA Technology (001/ KEPPHP-BATAN/X/2021). IVDMD was determined using the in vitro Ankom Daisy technique (Ankom Technology Corp, Fairport, New York, USA) (Ayaşan et al, 2020). Rumen fluids were collected from three local cattle (approximate live weight 280 kg) slaughtered at a local abattoir in South Tangerang, Banten, Indonesia.…”
Section: Determination Of In Vitro Digestibilitymentioning
confidence: 99%
“…Our laboratory used molecular biology techniques to successfully introduce the cellulase-expressing gene xg into Lactobacillus plantarum (LP) via genetic engineering technology, and successfully constructed cellulase-producing engineered lactic acid bacteria (LP-p11- celA - xg, xg ); their application on alfalfa silage resulted in positive results. These bacteria not only reduced the content of neutral detergent fiber, acid detergent fiber, and acid detergent lignin in alfalfa silage to a significant extent, but also effectively inhibited protein degradation, improved in vitro digestibility and gas production, and significantly improved the quality of alfalfa silage [ 10 ]. Fiber digestibility is the main factor limiting the efficient use of silage by ruminants.…”
Section: Introductionmentioning
confidence: 99%